2006
DOI: 10.1634/stemcells.2006-0562
|View full text |Cite
|
Sign up to set email alerts
|

A Scaleable and Defined System for Generating Neural Stem Cells from Human Embryonic Stem Cells

Abstract: The ability to differentiate human ESCs (hESCs) to defined lineages in a totally controlled manner is fundamental to developing cell-based therapies and studying human developmental mechanisms. We report a novel, scaleable, and widely applicable system for deriving and propagating neural stem cells from hESCs without the use of animal products, proprietary formulations, or genetic manipulation. This system provides a definitive platform for studying human neural development and has potential therapeutic implic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(101 citation statements)
references
References 67 publications
4
97
0
Order By: Relevance
“…37 Previous reports that HIF-1a interacts with Notch, 21 and that HIF-2a regulates Oct4, 22 might suggest that low O 2 would maintain pluripotency in ESCs and present a barrier to efficient neural induction and terminal differentiation. However, we observed that at 3% O 2 , efficient neuralisation was completed by 14 days, a timescale comparable to that at 20% O 2 , 14,33 indicating that a low O 2 environment does not adversely affect acquisition of a neural fate. Additionally, under basal conditions, significantly more NPCs were generated at 3% than at 20% O 2 , with a greater proportion of viable cells; a finding consistent with a previous study based on feeder and matrigel-maintained human ES cells, reporting a decrease in parthanatic cell death in neurectoderm derived at 3% O 2 .…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…37 Previous reports that HIF-1a interacts with Notch, 21 and that HIF-2a regulates Oct4, 22 might suggest that low O 2 would maintain pluripotency in ESCs and present a barrier to efficient neural induction and terminal differentiation. However, we observed that at 3% O 2 , efficient neuralisation was completed by 14 days, a timescale comparable to that at 20% O 2 , 14,33 indicating that a low O 2 environment does not adversely affect acquisition of a neural fate. Additionally, under basal conditions, significantly more NPCs were generated at 3% than at 20% O 2 , with a greater proportion of viable cells; a finding consistent with a previous study based on feeder and matrigel-maintained human ES cells, reporting a decrease in parthanatic cell death in neurectoderm derived at 3% O 2 .…”
Section: Discussionmentioning
confidence: 59%
“…There was no significant difference between the efficiency of neural conversion at 3 and 20% O 2 , with a neural identity acquired by D14 in both instances (Figure 1c), consistent with previous reports of a 2-week timescale for neural conversion of hESCs at 20% O 2 . 14,33,35,36 Neural conversion at 3% O 2 was robust, highly reliable and reproducible across two independent hESC Figure 1A). Growth curves confirmed a significant increase in numbers of NPCs generated at 3% compared with 20% O 2 , under basal culture conditions (Figure 2a Figure 1B).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…In fact, all animal products must be removed from the culturing condition, and there must be defined culture and media conditions in order to comply with GMP. Fortunately, both researchers 87,128,129 and biotechnology companies are producing media and supplements that are meeting this requirement. Unfortunately, the ingredients are proprietary, none of the companies will provide the ingredients (although the media are for sale), and very few of the scientists are willing at this point to share all of their knowledge.…”
Section: Proliferation and Differentiation Of Hescmentioning
confidence: 99%
“…Moreover, from a clinical point of view, protocols which emphasize on defined/human derived products for cell preparations prevail over methods using animal products. It has been shown that animal products increase the risk of non-human antigens expression and xeno infections (Joannides et al 2007). Our findings establish a simple and efficient protocol to enrich the adult rat SCs without the use of serum or other animal-derived products.…”
Section: Discussionmentioning
confidence: 63%